Unraveling the Molecular Basis of Mycosporine Biosynthesis in Fungi - Sepúlveda, Dionisia (2023)
The Phaffia rhodozyma UCD 67-385 genome harbors a 7873 bp cluster containing DDGS, OMT, and ATPG, encoding 2-desmethy-4-deoxygadusol synthase, O-methyl transferase, and ATPgrasp ligase, respectively, of the mycosporine glutaminol (MG) biosynthesis pathway. Homozygous deletion mutants of the entire cluster, single-gene mutants, and the ∆ddgs−/−;∆omt−/− and ∆omt−/−;∆atpg−/− double-gene mutants did not produce mycosporines. However, ∆atpg−/− accumulated the intermediate 4-deoxygadusol. Heterologous expression of the DDGS and OMT or DDGS, OMT, and ATPG cDNAs in Saccharomyces cerevisiae led to 4-deoxygadusol or MG production, respectively. Genetic integration of the complete cluster into the genome of the non-mycosporine-producing CBS 6938 wild-type strain resulted in a transgenic strain (CBS 6938_MYC) that produced MG and mycosporine glutaminol glucoside. These results indicate the function of DDGS, OMT, and ATPG in the mycosporine biosynthesis pathway. The transcription factor gene mutants ∆mig1−/−, ∆cyc8−/−, and ∆opi1−/− showed upregulation, ∆rox1−/− and ∆skn7−/− showed downregulation, and ∆tup6−/− and ∆yap6−/− showed no effect on mycosporinogenesis in glucose-containing medium. Finally, comparative analysis of the cluster sequences in several P. rhodozyma strains and the four newly described species of the genus showed the phylogenetic relationship of the P. rhodozyma strains and their differentiation from the other species of the genus Phaffia.